What do avatars want?. Issue 1 (1st November 2016) - Heller, Lynne
This article references the 'pictorial' and 'affective' turns in theory in order to discern 'what avatars want', a play on the cultural theorist W. J. T. Mitchell's ideas. By arguing that what avatars want is really what we want, I propose that 'truth' or 'real' has very little to do with how we feel about our avatar creations. So putting aside whether we want to suggest that an avatar is 'alive', their existence reveals our desires, yearnings, fears and insecurities. I concentrate on the intricacies of reading the avatar as an animated, performed image and our desire to inject it with subjectivity, while at the same time thinking of it as an object. The avatar entity need not be proven 'real' or 'alive' for us to feel it is. We have a 'reality hunger', as suggested by the writer David Shields, which needs to be fed with objects that seem sentient and brimming with emotions.